Click that sack! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Seventeen lots of quality gourmet coffee, good for almost 4 tonnes, were up for sale at Africa s first Internet coffee auction, held in Nairobi, Kenya, on 10 April 2002. They came from growers in from Ethiopia, Kenya, Tanzania and Uganda. Only two...